Blocked polyisocyanate crosslinking agent, method for preparing same and coating composition containing same
By reacting the polyisocyanate with β-acylaldehyde and further processing with (formaldehyde), a crosslinking agent with barrier properties was prepared, which solved the problem of poor fluidity, stability and curing effect of the coating in the prior art, and achieved high-performance coating curing.
Patent Information
- Application Number
- JP2022528240
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-15
- Filing Date
- 2020-11-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-11-09
AI Technical Summary
In the application of existing barrier polyisocyanate crosslinkers in automotive coatings, it is difficult to achieve good fluidity, storage stability and dual curing (free radical polymerization and reaction of isocyanate with polyacetate/ol) effects.
By reacting the polyisocyanate with β-acylaldehyde (β-diketone) and further reacting the product with the (formate) and the product of step i) a polyisocyanate crosslinker with barrier properties was prepared.
It achieves good fluidity, storage stability of polyisocyanate crosslinking agent in the coating, and supports dual curing reaction, which significantly improves the performance of the coating.
Abstract
Description
[Technical field]
[0001] The present invention relates to blocked polyisocyanate crosslinkers, methods for their preparation, and coating compositions containing such blocked polyisocyanate crosslinkers, more particularly to automotive coating compositions containing such blocked polyisocyanate crosslinkers. [Background technology]
[0002] Blocked polyisocyanates as curing agents (crosslinking agents) are widely used in the baking of automotive coating compositions. US6559264B1 discloses aliphatic and / or alicyclic polyisocyanates having A) 5-95 equivalent %, preferably 70-30 equivalent % of isocyanate groups blocked with (reacted with) acidic CH esters, B) 5-95 equivalent %, preferably 70-30 equivalent % of isocyanate groups blocked with (reacted with) 1,2,4-triazole, and C) 0-10 equivalent % of isocyanate groups blocked with (reacted with) another blocking agent different from A) and B), which contain 0.05-1.0 mol of formaldehyde in an integrated form relative to 100 equivalent % of blocked NCO groups. However, the amount of solvent is not reduced, and therefore, the problem of VOC (volatile organic compounds) exists. US2012 / 031629A1 discloses that aliphatic polyisocyanates, cycloaliphatic polyisocyanates, and aromatic polyisocyanates are blocked with a mixture of C,H-acidic groups and N,H-active hydrogen-containing compounds to provide blocked polyisocyanate compositions. Although the amount of solvent is reduced, the isocyanates and polyacrylates / polyols cannot react with each other. Summary of the Invention [Problem to be solved by the invention]
[0003] Thus, there remains a need for blocked polyisocyanate crosslinkers for coating compositions that have excellent flowability, high storage stability, and are capable of curing the coating composition via radical polymerization and / or reaction of an isocyanate with a polyacrylate / polyol. [Means for solving the problem]
[0004] In one aspect, the present invention provides a method for producing a method for treating a cancer cell comprising: a). at least one polyisocyanate selected from aliphatic polyisocyanates, cycloaliphatic polyisocyanates, and polyisocyanate-functional polymers; and b). at least one β-diketone; The present invention provides a blocked polyisocyanate crosslinking agent obtained from the reaction of components comprising:
[0005] In another aspect, the present invention provides a method for producing a method for the preparation of a pharmaceutical composition comprising the steps of: i) Reaction of polyisocyanates with β-diketones; and ii). Reaction of the resulting product obtained in step i) with a (meth)acrylate; The present invention provides a method for preparing a blocked polyisocyanate crosslinker, comprising:
[0006] In another aspect, the present invention provides a method for producing a composition comprising: A). at least one blocked polyisocyanate crosslinker of the present invention; and B). at least one reactive diluent. The present invention provides a coating composition comprising:
[0007] In another aspect, the present invention provides a method for producing a composition comprising: A). at least one blocked polyisocyanate crosslinker of the present invention; and C). at least one polyol. The present invention provides a coating composition comprising:
[0008] In another aspect, the present invention provides a method for producing a composition comprising: A). at least one blocked polyisocyanate crosslinker of the present invention; B). at least one reactive diluent; and C). at least one polyol. The present invention provides a coating composition comprising:
[0009] In a further aspect, the present invention provides a method for producing a method for treating a cancer cell comprising the steps of: A). at least one blocked polyisocyanate crosslinker of the present invention; B). at least one reactive diluent; and D). at least one unsaturated polyester. A coating composition comprising:
[0010] Detailed Description of the Invention Unless otherwise defined, all technical and scientific terms used herein have the meaning commonly understood by one of ordinary skill in the art to which this invention belongs. As used herein, the following terms have the meanings ascribed to them unless specified otherwise.
[0011] As used herein, the articles "a" and "an" refer to one or to more than one (i.e., to at least one) of the grammatical object of the article. By way of example, "an element" means one element or more than one element.
[0012] As used herein, the term "1K" refers to a composition having all of its ingredients in one package.
[0013] As used herein, the term "2K" refers to a composition that includes two components, each of which may also be a mixture of several compounds. The two components may be blended together as needed, or may be two separate packages that can be mixed at the time of use.
[0014] As used herein, the term "(poly)isocyanate" refers to a (poly)isocyanate having at least two NCO groups that react with an active hydrogen-containing compound.
[0015] As used herein, the term "blocked (poly)isocyanate" refers to a (poly)isocyanate that is unable to react until exposed to a specific unblocking temperature or agent.
[0016] As used herein, the term "reactive diluent" refers to a monomer that acts as a solvent for the resin and then reacts with components of the resin that have unsaturated groups.
[0017] As used herein, the term "solids" refers to the portion of the non-volatile material contained in a coating, paint or other suspension, that is the material remaining after the volatile solvent has evaporated.
[0018] The object of the present invention is to provide blocked polyisocyanate crosslinkers for 1K and 2K coating compositions which have excellent flowability, good storage stability and allow dual curing of the coating composition (radical polymerization and reaction of the isocyanate with polyacrylates / polyols).
[0019] Blocked Polyisocyanate Crosslinker The blocked polyisocyanate crosslinking agent according to the present invention is obtained from the reaction of components comprising: a) at least one polyisocyanate selected from aliphatic polyisocyanates, cycloaliphatic polyisocyanates, and polyisocyanate-functional polymers, and b) at least one β-diketone.
[0020] The polyisocyanate on which the blocked polyisocyanate is based is a known polyisocyanate containing aliphatically and / or cycloaliphatically bound isocyanate groups and / or polyisocyanate-functional polymers, with an isocyanate (NCO) group content of 10-50% by weight, preferably 15%-35%. Preferably, the polyisocyanate is at least one selected from hexamethylene diisocyanate, hexamethylene diisocyanate trimer, 4,4'-dicyclohexylmethane diisocyanate and polyisocyanate-functional aliphatic acrylic esters. Other isocyanate-based polyisocyanates can also be used, such as diisocyanatobutane-1,4,2,4-cyclohexane, 2,6-diisocyanato-1-methyl-cyclohexane, 2,5-bis-isocyanato-norbornane, 2,6-bis-isocyanato-norbornane, 3-isocyanatomethyl-1-methylcyclohexane, 4-isocyanatomethyl-1-methylcyclohexane, 1,4-bis-(2-isocyanatoprop-2-yl)benzene, 1,3-diisocyanatomethylbenzene, 1,3-bis-isocyanatomethylcyclohexane and 1,4-bis-isocyanatomethylcyclohexane.
[0021] The β-diketone is reacted with a portion of the NCO groups of the polyisocyanate. Preferably, the β-diketone is selected from the group consisting of 1,3-indandione, 1-(2-aminophenyl)decane-1,3-dione, 2'-O-methylcodione, 2,4,4',6-tetrahydroxydibenzoylmethane, 2,4-dioxopentanedioic acid, ethyl 2-oxocyclopentanecarboxylate, 2-[(2,6-dioxocyclohexyl)methyl]cyclohexane-1,3-dione, 2-[(4,4-dimethyl-2,6-dioxocyclohexyl)methyl]-5,5-dimethylcyclohexane-1,3-dione, 2-[1- (2,6-dioxocyclohexyl)-3-phenylprop-2-ynyl]cyclohexane-1,3-dione, 2-cyano-3-cyclopropyl-1-(2-mesyl-4-trifluoromethylphenyl)propane-1,3-dione, 3,5-dioxooctane diacid, 3,6-dihydroxycyclohexane-1,2,4,5-tetrone, 3-dehydro-scyllo-inosose, 3-fumarylpyruvic acid, 3-hydroxy-2,4-dioxopentyl phosphate, 3-maleylpyruvic acid, 3-undecylcyclo Hexane-1,2,4,5-tetrone, 4,6-dioxohept-2-enedioic acid, 4,6-dioxoheptanoic acid, 4-(2-aminophenyl)-2,4-dioxobutanoic acid, 4-(3-methyl-5-isoxazolyl)-5-phenylcyclohexane-1,3-dione, 4-[4-(3,5-dioxohexyl)phenylcarbamoyl]butyric acid, 4-fumarylacetoacetate, 4-maleylacetoacetate, 5,7-icosanedione, 5-(2,2-diferroylethen-1-yl)thalidomide (5-(2,2-dife ruloylethen-1-yl)thalidomide), 5-(2-furanyl)cyclohexane-1,3-dione, 5-(hydroxymethyl)-3-(1-oxohexadecyl)oxolane-2,4-dione, 5-ethylundecane-2,4-dione, 5-hydroxy-2,4-dioxopentanoic acid, 6,8-icosanedione, 6-gingerdione, acetylacetone, acetylpyruvic acid, α-acetylbutyrolactone, anisindione, berkeleydione, berkeleytrione, bicyclo[2.2.2] Octane-2,6-dione, bicyclopyrone, bisdemethoxycurcumin, clethodim, curcumin, cyclohexane-1,3-dione, cyclopentane-1,3-dione, cycloxydim, demethoxycurcumin, dibenzoylmethane, dihydrocurcumin, hentriacontane-14,16-dione, ricodione, ninhydrin, nonane-4,6-dione, phenindione, tenuazonic acid, tetrahydrocurcumin and tritriacontane-16,18-dione. More preferably, the β-diketone is at least one selected from ethyl 2-oxocyclopentanecarboxylate and / or α-acetylbutyrolactone.
[0022] Preferably, at least one (meth)acrylate having a sulfhydryl group and / or an amino group and / or a hydroxyl group is added to react with the NCO groups of the polyisocyanate. The β-diketone consumes all the NCO groups of the polyisocyanate together with the (meth)acrylate. Preferably, the (meth)acrylate is 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 3- and 4-hydroxybutyl acrylate, 3- and 4-hydroxybutyl methacrylate, 6-hydroxyethyl acrylate, 6-hydroxyethyl methacrylate, 3-hydroxy-2-ethylhexyl acrylate, 3-hydroxy-2-ethylhexyl methacrylate, 2-hydroxypropyl methacrylate, 3-(acryloyl)-2-hydroxypropyl methacrylate, pentaerythritol triacrylate. , pentaerythritol trimethacrylate, 2-aminoethyl acrylate, 2-aminoethyl methacrylate, 2-(tert-butylamino)ethyl acrylate, 2-(tert-butylamino)ethyl methacrylate, N,N-diethylaminoethyl acrylate, N,N-diethylaminoethyl methacrylate, N,N-dimethylaminoethyl acrylate, N,N-dimethylaminoethyl methacrylate, 2,2,6,6-tetramethyl-4-piperidyl acrylate, and 2,2,6,6-tetramethyl-4-piperidyl methacrylate. Mixtures of these may also be used. And more preferably, the (meth)acrylate is at least one selected from 2-(tert-butylamino)ethyl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxyethyl acrylate.
[0023] Surprisingly, it has been found that by blocking polyisocyanates with a combination of β-diketones and (meth)acrylates, the resulting blocked polyisocyanate crosslinkers have excellent flowability, good storage stability and are applicable for dual cure (radical polymerization and reaction of isocyanates with polyacrylates / polyols) of automotive coating compositions.
[0024] Preferably, the molar ratio of β-diketone to (meth)acrylate is 1:10 to 10:1, more preferably 1:2 to 2:1. A lower ratio of β-diketone or a higher ratio of (meth)acrylate tends to result in a blocked polyisocyanate crosslinking agent that provides a non-tacky coating layer.
[0025] When said (meth)acrylate is present, the blocked polyisocyanate crosslinker is prepared by the following steps: i) reacting a polyisocyanate with a β-diketone; and ii) reacting the resulting product obtained in step i) with a (meth)acrylate.
[0026] Coating Composition The blocked polyisocyanate crosslinker can be used in 1K and 2K coating compositions. For example, a coating composition can be prepared that includes at least one blocked polyisocyanate crosslinker of the present invention and at least one reactive diluent. In another example, a coating composition can be prepared that includes at least one blocked polyisocyanate crosslinker of the present invention and at least one polyol. In another example, a coating composition can be prepared that includes at least one blocked polyisocyanate crosslinker of the present invention, at least one reactive diluent; and at least one polyol. And in a further example, a coating composition can be prepared that includes at least one blocked polyisocyanate crosslinker of the present invention, at least one reactive diluent, and at least one unsaturated polyester.
[0027] Preferably, the reactive diluent is at least one selected from (meth)acrylates, and is selected from methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, amyl acrylate, amyl methacrylate, hexyl acrylate, hexyl methacrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-ethylhexyl methacrylate, 3,3,5-trimethylhexyl acrylate, 2-hydroxyethyl methacrylate, 3,3,5-trimethylhexyl methacrylate, cyclohexyl ... and at least one selected from the group consisting of ethyl methacrylate, isobornyl acrylate, isobornyl methacrylate, norbornyl acrylate, norbornyl methacrylate, adamantyl acrylate, 1,4-butanediol diacrylate, 1,4-butanediol dimethacrylate, 2-(tert-butylamino)ethyl methacrylate, 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, ethoxylated diacrylate, ethoxylated dimethacrylate, ethoxylated triacrylate, ethoxylated trimethacrylate, pentaerythritol tetraacrylate, pentaerythritol tetramethacrylate, di(trimethylolpropane)tetraacrylate, and di(trimethylolpropane)tetramethacrylate. More preferably, the (meth)acrylate is at least one selected from 2-(tert-butylamino)ethyl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxyethyl acrylate.
[0028] The polyol may be any known polyether polyol and / or polyester polyol and / or polyacrylate-based polyol, such as polyethylene oxide, polyethylene glycol and polypropylene glycol. The polyol is used in combination with a polyisocyanate to produce a polyurethane.
[0029] The unsaturated polyester has double bonds in the main chain and / or side chains and hydroxyl groups and / or carboxyl groups.Preferably, the unsaturated polyester can be selected from maleic anhydride-based unsaturated polyesters, itaconic acid-based unsaturated polyesters, fumaric acid-based unsaturated polyesters, trans-aconitic acid-based unsaturated polyesters and hexahydrophthalic anhydride-based unsaturated polyesters.
[0030] In order to improve the thixotropic behavior, additives such as high solid content sag control agents can be added into the coating composition. The sag control agent used in the present invention has a solid content of 90% by weight or more based on the total weight of the sag control agent. Preferably, the sag control agent is at least one selected from benzylamine and hexamethylene diisocyanate based sag control agents, methoxypropylamine and hexamethylene diisocyanate trimer based sag control agents.
[0031] β-diketones, such as ethyl 2-oxocyclopentanecarboxylate, are deblocked at a temperature of 140°C, and the polyisocyanates obtained after deblocking react with polyacrylates / polyols, and the ethyl 2-oxocyclopentanecarboxylate initiates the free radical polymerization reaction of the reactive diluent after being activated by atmospheric oxygen. Thus, the coating has very low VOC content, and the coating layer obtained after curing exhibits good performance in hardness, solvent resistance, elasticity, adhesion and elongation.
[0032] Embodiment The following embodiments are used to describe the present invention in more detail.
[0033] The first embodiment is as follows: a). at least one polyisocyanate selected from aliphatic polyisocyanates, cycloaliphatic polyisocyanates, and polyisocyanate-functional polymers; and b). at least one β-diketone; The blocked polyisocyanate crosslinking agent is obtained from the reaction of components including:
[0034] A second embodiment is the blocked polyisocyanate crosslinker according to the first embodiment, wherein the polyisocyanate is preferably at least one polyisocyanate selected from hexamethylene diisocyanate, hexamethylene diisocyanate trimer, 4,4'-dicyclohexylmethane diisocyanate and polyisocyanate-functional aliphatic acrylic esters.
[0035] In a third embodiment, the β-diketone is selected from the group consisting of 1,3-indandione, 1-(2-aminophenyl)decane-1,3-dione, 2'-O-methylcodione, 2,4,4',6-tetrahydroxydibenzoylmethane, 2,4-dioxopentanedioic acid, ethyl 2-oxocyclopentanecarboxylate, 2-[(2,6-dioxocyclohexyl)methyl]cyclohexane-1,3-dione, 2-[(4,4-dimethyl-2,6-dioxocyclohexyl)methyl]-5,5-dimethylcyclohexane-1,3-dione, 2- [1-(2,6-dioxocyclohexyl)-3-phenylprop-2-ynyl]cyclohexane-1,3-dione, 2-cyano-3-cyclopropyl-1-(2-mesyl-4-trifluoromethylphenyl)propane-1,3-dione, 3,5-dioxooctane dioic acid, 3,6-dihydroxycyclohexane-1,2,4,5-tetrone, 3-dehydro-scyllo-inosose, 3-fumarylpyruvic acid, 3-hydroxy-2,4-dioxopentyl phosphate, 3-maleylpyruvic acid, 3-undecylcyanopyruvic acid, Cyclohexane-1,2,4,5-tetrone, 4,6-dioxohept-2-enedioic acid, 4,6-dioxoheptanoic acid, 4-(2-aminophenyl)-2,4-dioxobutanoic acid, 4-(3-methyl-5-isoxazolyl)-5-phenylcyclohexane-1,3-dione, 4-[4-(3,5-dioxohexyl)phenylcarbamoyl]butyric acid, 4-fumarylacetoacetate, 4-maleylacetoacetate, 5,7-icosanedione, 5-(2,2-diferroylethen-1-yl)thalidomide (5-(2,2-dif eruloylethen-1-yl)thalidomide), 5-(2-furanyl)cyclohexane-1,3-dione, 5-(hydroxymethyl)-3-(1-oxohexadecyl)oxolane-2,4-dione, 5-ethylundecane-2,4-dione, 5-hydroxy-2,4-dioxopentanoic acid, 6,8-icosanedione, 6-gingerdione, acetylacetone, acetylpyruvic acid, α-acetylbutyrolactone, anisindione, berkeleydione, berkeleytrione, bicyclo[2.2.2] The blocked polyisocyanate crosslinker according to any one of embodiments 1 to 2, which is at least one selected from octane-2,6-dione, bicyclopyrone, bisdemethoxycurcumin, clethodim, curcumin, cyclohexane-1,3-dione, cyclopentane-1,3-dione, cycloxydim, demethoxycurcumin, dibenzoylmethane, dihydrocurcumin, hentriacontane-14,16-dione, ricodione, ninhydrin, nonane-4,6-dione, phenindione, tenuazonic acid, tetrahydrocurcumin, and tritriacontane-16,18-dione.
[0036] A fourth embodiment is a blocked polyisocyanate crosslinker according to embodiment 3, wherein the β-diketone is preferably ethyl 2-oxocyclopentanecarboxylate and / or α-acetylbutyrolactone.
[0037] A fifth embodiment is a blocked polyisocyanate crosslinker according to any one of the first to fourth embodiments, further comprising at least one (meth)acrylate having a sulfhydryl group and / or an amino group and / or a hydroxyl group.
[0038] In a sixth embodiment, the (meth)acrylate is 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 3- and 4-hydroxybutyl acrylate, 3- and 4-hydroxybutyl methacrylate, 6-hydroxyethyl acrylate, 6-hydroxyethyl methacrylate, 3-hydroxy-2-ethylhexyl acrylate, 3-hydroxy-2-ethylhexyl methacrylate, 2-hydroxypropyl methacrylate, 3-(acryloyl)-2-hydroxypropyl methacrylate, pentaerythritol triacrylate, pentaerythritol trime The blocked polyisocyanate crosslinker according to embodiment 5 is at least one selected from N,N-dimethylaminoethyl acrylate, N,N-dimethylaminoethyl methacrylate, N,N-dimethylaminoethyl acrylate, N,N-dimethylaminoethyl methacrylate, 2,2,6,6-tetramethyl-4-piperidyl acrylate, and 2,2,6,6-tetramethyl-4-piperidyl methacrylate. Mixtures of these may also be used.
[0039] A seventh embodiment is a blocked polyisocyanate crosslinker according to embodiment 6, wherein the (meth)acrylate is preferably at least one selected from 2-(tert-butylamino)ethyl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxyethyl acrylate.
[0040] An eighth embodiment is the blocked polyisocyanate crosslinking agent according to any one of embodiments 5 to 7, wherein the molar ratio of the β-diketone to the (meth)acrylate is 1:10 to 10:1, preferably 1:2 to 2:1.
[0041] A ninth embodiment is a method for preparing a blocked polyisocyanate crosslinker according to any one of embodiments 5 to 8, comprising the steps of: i) Reaction of polyisocyanates with β-diketones; and ii). Reaction of the resulting product obtained in step i) with a (meth)acrylate; The method includes:
[0042] The tenth embodiment is as follows. A). at least one blocked polyisocyanate crosslinker according to any one of embodiments 1 to 9; and B). at least one reactive diluent. A coating composition comprising:
[0043] The eleventh embodiment is as follows. A). at least one blocked polyisocyanate crosslinker according to any one of embodiments 1 to 9; and C). at least one polyol, A coating composition comprising:
[0044] The twelfth embodiment is as follows: A). at least one blocked polyisocyanate crosslinker according to any one of embodiments 1-9; B). at least one reactive diluent; and C). at least one polyol. A coating composition comprising:
[0045] The thirteenth embodiment is as follows: A). at least one blocked polyisocyanate crosslinker according to any one of embodiments 1-9; B). at least one reactive diluent; and D). at least one unsaturated polyester. A coating composition comprising:
[0046] A fourteenth embodiment is a coating composition according to the thirteenth embodiment, further comprising at least one sag control agent having a solids content of 90% or more by weight, based on the total weight of the sag control agent.
[0047] Working Example The invention will now be described with reference to examples which are not intended to be limiting.
[0048] Example 1: Preparation of a blocked polyisocyanate crosslinker 330.2 g (0.51 mol) of HDI (hexamethylene diisocyanate)-trimer (Evonik Desmodur N3000) and 20 mg of the catalyst sodium methoxylate were placed in a flask under nitrogen. 80 g (0.16 mol) of ethyl 2-oxocyclopentanecarboxylate were added dropwise at room temperature, while the reaction temperature eventually rose to 40 °C. External heating to 80 °C was continued under nitrogen with stirring until the calculated NCO content was reached. The reaction mixture was cooled to room temperature and 189.8 g (0.31 mol) of 2-(tert-butylamino)ethyl methacrylate (Sinopharm) was added dropwise, while the temperature was kept between 35 and 45 °C until the NCO content was 0%. 600 g of a slightly yellowish liquid was obtained, which was further diluted with a mixture of reactive diluents HDDA and TMPTA in different ratios (from 100:0% to 0:100%). The residual initiator content was below the HPLC detection limit of 0.01%.
[0049] Example 2: Preparation of a blocked polyisocyanate crosslinker 66.04 g (0.34 mol) HDI-trimer (Evonik Desmodur N3000) and 20 mg catalyst sodium methoxylate were placed in a flask under nitrogen atmosphere. 16 g (0.1 mol) AcBL were added dropwise within 30 min at 40 °C. External heating to 80 °C and stirring continued under nitrogen until the calculated NCO content was reached. The reaction mixture was cooled to room temperature and 38 g (0.2 mol) 2-(tert-butylamino)ethyl methacrylate (Sinopharm) were added dropwise, keeping the temperature between 35-45 °C until the NCO content was 0%. 120 g slightly yellowish liquid was obtained, which was further diluted with a mixture of reactive diluents HDDA and TMPTA in different ratios (from 100:0% to 0:100%). The residual initiator content was below the HPLC detection limit of 0.01%.
[0050] Example 3: Preparation of a blocked polyisocyanate crosslinker 254.3 g (1.3 mol) HDI-trimer (Evonik Desmodur N3000) and 80 mg catalyst sodium methoxylate were placed in a flask under nitrogen atmosphere. 64.03 g (0.41 mol) EOC were added dropwise within 30 min at 40 °C. External heating to 80 °C and stirring continued under nitrogen until the calculated NCO content. The reaction mixture was cooled to room temperature and 38 g (0.2 mol) 2-hydroxyethyl methacrylate (HEMA) were added dropwise, keeping the temperature between 35 and 45 °C until the NCO content was 0%. 260 g slightly yellowish liquid was obtained, which was further diluted with a mixture of reactive diluents HDDA and TMPTA in different ratios (from 100:0% to 0:100%). The residual initiator content was below the HPLC detection limit of 0.01%.
[0051] Example 4: Preparation of a blocked polyisocyanate crosslinker 72.1 g (0.37 mol) HDI-trimer (Evonik Desmodur N3000) and 20 mg catalyst sodium methoxylate were placed in a flask under nitrogen atmosphere. 34.9 g (0.22 mol) AcBL were added dropwise within 30 min at 40 °C. External heating to 80 °C and stirring continued under nitrogen until the calculated NCO content was reached. The reaction mixture was cooled to room temperature and 13 g (0.11 mol) 2-hydroxyethyl acrylate (HEA) were added dropwise, keeping the temperature between 35 and 45 °C until the NCO content was 0%. 120 g slightly yellowish liquid was obtained, which was further diluted with a mixture of reactive diluents HDDA and TMPTA in different ratios (from 100:0% to 0:100%). The residual initiator content was below the HPLC detection limit of 0.01%.
[0052] Example 5: Preparation of a blocked polyisocyanate crosslinker 128.6 g (0.49 mol) of HMDI and 80 mg of catalyst sodium methoxylate were placed in a flask under nitrogen atmosphere. 69.6 g (0.45 mol) of EOC were added dropwise within 30 min at 40 °C. External heating to 80 °C was continued with stirring under nitrogen until the calculated NCO content was reached. The reaction mixture was cooled to room temperature and 51.7 g (0.45 mol) of 2-hydroxyethyl acrylate (HEA) was added dropwise, keeping the temperature between 35 and 45 °C until the NCO content was 0%. 250 g of a slightly yellowish liquid was obtained, which was further diluted with a mixture of reactive diluents HDDA and TMPTA in different ratios (from 100:0% to 0:100%). The residual initiator content was below the HPLC detection limit of 0.01%.
[0053] Example 6: Preparation of a blocked polyisocyanate crosslinker 83.8 g (0.29 mol) of Laromer PR900 and 50 mg of catalyst sodium methoxylate were placed in a flask under nitrogen atmosphere. 16.83 g (0.13 mol) of AcBL was added dropwise within 30 min at 40 °C. External heating to 80 °C was continued with stirring under nitrogen until the calculated NCO content was reached. The reaction mixture was cooled to room temperature and 24.36 g (0.13 mol) of 2-hydroxyethyl acrylate (HEA) was added dropwise, keeping the temperature between 35-45 °C until the NCO content was 0%. 125 g of a slightly yellowish highly viscous liquid was obtained, which was further diluted with a mixture of reactive diluents HDDA and TMPTA in different ratios (from 100:0% to 0:100%). The residual initiator content was below the HPLC detection limit of 0.01%.
[0054] Example 7: Preparation of a blocked polyisocyanate crosslinker 162.78 g (0.56 mol) of Laromer PR900 and 10 mg of catalyst sodium methoxylate were placed in a flask under nitrogen atmosphere. 39.9 g (0.26 mol) of EOC were added dropwise within 30 min at 40 °C. External heating to 80 °C was continued with stirring under nitrogen until the calculated NCO content was reached. The reaction mixture was cooled to room temperature and 47.32 g (0.13 mol) of 2-hydroxyethyl acrylate (HEA) was added dropwise, keeping the temperature between 35-45 °C until the NCO content was 0%. 125 g of a slightly yellowish highly viscous liquid was obtained, which was further diluted with a mixture of reactive diluents HDDA and TMPTA in different ratios (from 100:0% to 0:100%). The residual initiator content was below the HPLC detection limit of 0.01%.
[0055] Example 8: Coating composition and coating layer obtained after curing 5.1 g of blocked polyisocyanate crosslinker from example 1 is added to 8.6 g of OH-functionalized polyacrylic, 300 mg of amino catalyst and 300 mg of BYK333, mixed and stirred until a homogeneous mixture is obtained. The mixture is applied to a tin test panel by doctor blade or spray and baked at 140°C for 20 minutes to obtain a tack-free film. After 3 days of post-cure, single layer tests for performance check were carried out by evaluating hardness (Koenig pendulum), crosslink density (MEK double rub test) and bending performance (cone bend test). The tack-free and colorless coating films had a dry film thickness of 30-50 μm, K-pendulum more than 168 times and MEK double rub value more than 80 times. Cone bend tests at all test diameters (diameters from 3.2 to 38.1 mm) showed no cracks in the respective coating layers.
[0056] Example 9: Coating composition and coating layer obtained after curing 1.0 g of blocked polyisocyanate crosslinker from example 1 was added to 9 g of different mixtures of TMPTA and HDDA (from 10:1 to 1:1 and 1:10), 200 mg of BYK333, mixed and stirred until a homogeneous mixture was obtained. The mixture was applied to a tin test panel by doctor blade or spray and baked at 140 °C for 20 min to obtain a tack-free film. After 3 days of post-cure, single layer tests for performance check were carried out by evaluating hardness (Koenig pendulum), crosslink density (MEK double rub test) and bending performance (cone bend test). The tack-free and colorless coating films had a dry film thickness of 30-50 μm, K-pendulum more than 170 times and MEK double rub value more than 100 times. The cone bend test at all test diameters (diameters from 3.2 to 38.1 mm) showed no cracks in the respective coating layers.
[0057] Example 10: Coating composition and coating layer obtained after curing 5.1 g of blocked polyisocyanate crosslinker from example 1 was added to 13 g of TMPTA, and 8.6 g of OH-functionalized polyacrylic, 200 mg of amino catalyst, 100 mg of Mn08 and 300 mg of BYK333, mixed and stirred until a homogeneous mixture was obtained. The mixture was applied to a tin test panel by doctor blade or spray and baked at 140°C for 20 minutes to obtain a tack-free film. After 3 days of post-cure, single layer tests for performance check were carried out by evaluating hardness (Koenig pendulum), crosslink density (MEK double rub test) and bending performance (cone bend test). The tack-free and colorless coating films had a dry film thickness of 30-50 μm, K-pendulum more than 168 times, MEK double rub value more than 400 times. Cone bend tests at all test diameters (diameters from 3.2 to 38.1 mm) showed no cracks in the respective coating layers.
[0058] Example 11: Coating composition and coating layer obtained after curing 1 g of blocked polyisocyanate crosslinker from Example 3 is added to 4.5 g of TMPTA, 4.5 g of OH-functionalized polyacrylic, and 300 mg of BYK333, mixed and stirred until a homogeneous mixture is obtained. The mixture is applied to a tin test panel by doctor blade or spray and baked at 140°C for 20 minutes to obtain a tack-free film. After 3 days of post-cure, single layer tests for performance check were carried out by evaluating hardness (Koenig pendulum), crosslink density (MEK double rub test) and bending performance (cone bend test). The tack-free and colorless coating films had a dry film thickness of 30-50 μm, K-pendulum more than 154 times, MEK double rub value more than 400 times. Cone bend tests at all test diameters (diameters from 3.2 to 38.1 mm) showed no cracks in the respective coating layers.
[0059] Example 12: Coating composition and coating layer obtained after curing 1 g of blocked polyisocyanate crosslinker from Example 6 is added to 4.5 g of TMPTA, and 4.5 g of OH-functionalized polyacrylic, 200 mg of BYK333, mixed and stirred until a homogeneous mixture is obtained. The mixture is applied to a tin test panel by doctor blade or spray and baked at 140 °C for 20 minutes to obtain a tack-free film. After 3 days of post-cure, single layer tests for performance check were carried out by evaluating hardness (Koenig pendulum), crosslink density (MEK double rub test) and bending performance (cone bend test). The tack-free and colorless coating films had a dry film thickness of 30-50 μm, K-pendulum more than 175 times, MEK double rub value more than 300 times. Cone bend tests at all test diameters (diameters from 3.2 to 38.1 mm) showed no cracks in the respective coating layers.
[0060] Example 13: Preparation of unsaturated polyester 210g trimethylolpropane, 503g itaconic acid, 329g 1,4-butanediol, 12g xylene, 0.5g MEHQ and 1.5g BHT are added to the reactor and heated to 100°C and held for 60 minutes. The temperature is increased to 160°C and held for an additional hour, then increased to 230°C and held for 2 hours. Xylene is distilled during the reaction. Cool to 80°C and add 322g hexohydrophthalic anhydride, 100mg BHT and 80mg MEHQ (hydroquinone monomethyl ether) to the mixture and heat to 140°C for several hours. 623g Cadura E10P, 100mg BHT and 80mg MEHQ are added to the reaction mixture over 1.5 hours, cooled to 40°C and 500g trimethylolpropane triacrylate and 500g 1,6-hexanediol diacrylate are added. The reaction yields a solvent-free low viscosity unsaturated polyester resin (67% in reactive diluent) with an acid value of 10-50mg KOH / g, a hydroxy value of 100-300mg KOH / g and a Tg (glass transition temperature) of -55°C.
[0061] Example 14: Preparation of unsaturated polyester 189g trimethylolpropane, 535g hexohydrophthalic anhydride, 296g 1,4-butanediol and 11g xylene are placed in a reactor and heated to 100°C and held for 60 minutes. The temperature is increased to 160°C and held for an additional hour, then increased to 230°C and held for 2 hours. Xylene is distilled during the reaction. Cool to 80°C and add 280g itaconic acid, 900mg BHT and 500mg MEHQ to the mixture and heat to 140°C for several hours. 461g Cadura E10P, 300mg BHT and 150mg MEHQ are added to the reaction mixture over 1.5 hours, cooled to 40°C and add 233g trimethylolpropane triacrylate and 233g 1,6-hexanediol diacrylate. This reaction produces a solvent-free, low viscosity unsaturated polyester resin (80% in reactive diluent) with an acid value of 10-50 mgKOH / g, a hydroxyl value of 100-300 mgKOH / g and a Tg (glass transition temperature) of -26°C.
[0062] Example 15: Coating composition and coating layer obtained after curing For a typical 2K system, composition A (160 g trimethylolpropane triacrylate, 100 g 1,6-hexamethylene diacrylate, 20 g butyl acetate, 150 g blocked polyisocyanate crosslinker from example 1 and 125 g unsaturated polyester from example 13) is added to composition B (1.2 g catalyst 9001, 166 mg catalyst Borchers Deca Manganese 8, 1.1 g BYK378 and 5.5 g BYK410) and mixed and stirred until a homogeneous mixture is obtained. The VOC value of the coating composition was measured to be 105 g / L. The mixture was spray applied to a tin test panel and baked at 140° C. for 20 minutes to obtain a tack-free film. After 3 days of post-cure, single layer tests for performance check were performed by evaluating hardness (Koenig pendulum), crosslink density (MEK double rub test) and bending performance (cone bending test). The tack-free, colorless coating films had dry thicknesses ranging from 25 to 60 μm with K-pendulum values of greater than 98 and MEK double rub values of greater than 400. Cone bend tests at all test diameters (diameters from 3.2 to 38.1 mm) showed no cracks in the individual coating layers.
[0063] Example 16: Coating composition and coating layer obtained after curing For a typical 2K system, composition A (160 g trimethylolpropane triacrylate, 100 g 1,6-hexamethylene diacrylate, 20 g butyl acetate, 150 g blocked polyisocyanate crosslinker from example 1 and 125 g unsaturated polyester from example 14) is added to composition B (1.2 g catalyst 9001, 166 mg catalyst Borchers Deca Manganese 8, 1.1 g BYK378 and 5.5 g BYK410) and mixed and stirred until a homogeneous mixture is obtained. The VOC value of the coating composition was measured to be 103 g / L. The mixture was spray applied to a tin test panel and baked at 140° C. for 20 minutes to obtain a tack-free film. After 3 days of post-cure, single layer tests for performance check were performed by evaluating hardness (Koenig pendulum), crosslink density (MEK double rub test) and bending performance (cone bending test). The tack-free, colorless coating films had dry thicknesses ranging from 25 to 60 μm with K-pendulum values of greater than 84 and MEK double rub values of greater than 450. Cone bend tests at all test diameters (diameters from 3.2 to 38.1 mm) showed no cracks in the individual coating layers.
[0064] Example 17: Preparation of high solids sag suppressant 782 g (3.5 mol) of 1,6-hexanediol diacrylate, 261 g (0.9 mol) of trimethylolpropane triacrylate were pre-charged in a canister and started to dissolve at 500 rpm. A mixture of 27.4 g (0.3 mol) of benzylamine and 67 g of butyl acetate was added, the mixing speed was increased to 2000 rpm, and mixing was continued for an additional 2 minutes. 21.2 g (0.13 mol) of hexamethylene diisocyanate in 41 g of butyl acetate was added over 10 minutes, and mixing was continued for an additional 2 minutes after addition was complete. A SCA solution containing 4% diurea crystals and 9% butyl acetate in reactive diluent (HDDA:TMPTA = 75:25) was obtained as a white cloudy solution exhibiting a paste-like behavior (total solids of active diurea crystals + reactive diluent = 91%). The viscosities of the solutions were η, respectively. 1 (shear rate = 1000 s -1 )=64mPas and η2 (shear rate = 1s -1 )=5118mPas.
[0065] Example 18: Preparation of high solids sag inhibitor 437 g (1.9 mol) of 1,6-hexanediol diacrylate was pre-charged in a can and started to dissolve at 500 rpm. A mixture of 4.1 g (0.05 mol) of methoxypropylamine and 25 g of butyl acetate was added and the mixing speed was increased to 2000 rpm and stirred for an additional 2 minutes. 9 g of Desmodur N3300 in 25 g of butyl acetate was added over 10 minutes and stirring was continued for an additional 2 minutes after addition was complete. A SCA solution containing 2.5% diurea crystals and 10% butyl acetate in reactive diluent (HDDA) was obtained as a clear solution exhibiting a pasty behavior (total solids of active diurea crystals + reactive diluent = 90%). The viscosities of the solutions were η, respectively. 1 (shear rate = 1000 s -1 )=32mPas and η 2 (shear rate = 1s -1 )=1828mPas.
[0066] Example 19: Preparation of high solids sag inhibitor 437 g (1.5 mol) of trimethylolpropane triacrylate was pre-charged in a can and started to dissolve at 500 rpm. A mixture of 4.1 g (0.05 mol) of methoxypropylamine and 25 g of butyl acetate was added and the mixing speed was increased to 2000 rpm and stirred for an additional 2 minutes. 9 g of Desmodur N3300 in 25 g of butyl acetate was added over 10 minutes and stirring was continued for an additional 2 minutes after addition was complete. A SCA solution containing 2.6% diurea crystals and 10% butyl acetate in reactive diluent (HDDA) was obtained as a clear solution exhibiting a pasty behavior (total solids of active diurea crystals + reactive diluent = 90%). The viscosities of the solutions were η, respectively. 1 (shear rate = 1000 s -1 )=80mPas and η 2 (shear rate = 1s -1 )=4473mPas.
[0067] Example 20: Preparation of high solids sag suppressant 437 g (1.9 mol) of 1,6-hexanediol diacrylate was pre-charged in a can and started to dissolve at 500 rpm. A mixture of 9.5 g (0.1 mol) of methoxypropylamine and 28 g of butyl acetate was added and the mixing speed was increased to 2000 rpm and mixed for an additional 2 minutes. 8.8 g (0.05 mol) of hexamethylene diisocyanate in 17 g of butyl acetate was added over 10 minutes and mixing was continued for an additional 2 minutes after addition was complete. A SCA solution containing 3.7% diurea crystals and 9% butyl acetate in reactive diluent (HDDA) was obtained as a white cloudy solution exhibiting a paste-like behavior (total solids of active diurea crystals + reactive diluent = 91%). The viscosities of the solutions were η, respectively. 1 (shear rate = 1000 s -1 )=22mPas and η 2 (shear rate = 1s -1 )=3266 mPas.
[0068] Example 21: Coating composition and coating layer obtained after curing For a typical 2K system, composition A (6 g trimethylolpropane triacrylate, 15 g blocked polyisocyanate crosslinker from Example 1, 2 g butyl acetate, and 20 g sag control agent from Example 17 and 12 g unsaturated polyester from Example 14) is added to composition B (0.1 g catalyst 9001, 17 mg catalyst Borchers Deca Manganese 8, 0.1 g BYK378) and mixed and stirred until a homogenous mixture is obtained. The coating composition has a low shear viscosity to high shear viscosity ratio η 2 (shear rate = 1s -1 ) / η 1 (shear rate = 1000 s -1The coating composition showed thixotropic behavior with a K-pendulum > 6. The VOC value of the coating composition was measured to be 160 g / L. The mixture was spray applied to tin test panels and baked at 140 °C for 20 min to obtain a tack-free film. After 3 days of post-cure, single layer tests for performance check were carried out by evaluating hardness (Koenig's pendulum), crosslink density (MEK double rub test) and bending performance (cone bend test). The tack-free and colorless coating films had a dry film thickness of 25-60 μm with K-pendulum > 56 and MEK double rub values > 120. The cone bend test at all test diameters (diameters from 3.2 to 38.1 mm) showed no cracks in the respective coating layers.
[0069] Example 22: Coating composition and coating layer obtained after curing For a typical 2K system, composition A (6 g of 1,6-hexanediol diacrylate, 15 g of blocked polyisocyanate crosslinker, 2 g of butyl acetate, and 20 g of sag control agent from Example 19 and 12 g of unsaturated polyester from Example 14) is added to composition B (0.1 g of catalyst 9001, 17 mg of catalyst Borchers Deca Manganese 8, 0.1 g of BYK378) and mixed and stirred until a homogeneous mixture is obtained. The coating composition has a low shear viscosity to high shear viscosity ratio η 2 (shear rate = 1s -1 ) / η 1 (shear rate = 1000 s -1The coating composition showed thixotropic behavior with a K-pendulum > 6. The VOC value of the coating composition was measured to be 103 g / L. The mixture was spray applied to tin test panels and baked at 140 °C for 20 min to obtain a tack-free film. After 3 days of post-cure, single layer tests for performance check were carried out by evaluating hardness (Koenig pendulum), crosslink density (MEK double rub test) and bending performance (cone bend test). The tack-free and colorless coating films had a dry film thickness of 25-60 μm with K-pendulum > 84 and MEK double rub values > 400. The cone bend test at all test diameters (diameters from 3.2 to 38.1 mm) showed no cracks in the respective coating layers.
[0070] Example 23: Coating composition and coating layer obtained after curing For a typical 2K system, composition A (6 g trimethylolpropane triacrylate, 15 g blocked polyisocyanate crosslinker from Example 1, 2 g butyl acetate, and 20 g sag control agent from Example 20 and 12 g unsaturated polyester from Example 14) is added to composition B (0.1 g catalyst 9001, 17 mg catalyst Borchers Deca Manganese 8, 0.1 g BYK378) and mixed and stirred until a homogenous mixture is obtained. The coating composition has a low shear viscosity to high shear viscosity ratio η 2 (shear rate = 1s -1 ) / η 1 (shear rate = 1000 s -1)>6. The VOC value of the coating composition was measured to be 132 g / L. The mixture was spray applied to tin test panels and baked at 140°C for 20 minutes to obtain a tack-free film. After 3 days of post-cure, single layer tests for performance check were carried out by evaluating hardness (Koenig's pendulum), crosslink density (MEK double rub test) and bending performance (cone bend test). The tack-free and colorless coating films had a dry film thickness of 25-60 μm, K-pendulum of more than 84 and MEK double rub value of more than 400. The cone bend test at all test diameters (diameters from 3.2 to 38.1 mm) showed no cracks in the respective coating layers.
[0071] Example 24: Coating composition and coating layer obtained after curing For a typical 2K system, composition A (6 g trimethylolpropane triacrylate, 15 g blocked polyisocyanate crosslinker from example 1, 2 g butyl acetate, and 20 g sag control agent from example 17 and 12 g unsaturated polyester from example 14) is added to composition B (0.1 g catalyst 9001, 17 mg catalyst Borchers Deca Manganese 8, 0.1 g BYK378) and mixed and stirred until a homogeneous mixture is obtained. The VOC value of the coating composition was measured to be 132 g / L. The mixture was spray applied to a tin test panel and baked at 140°C for 20 minutes to obtain a tack-free film. After 3 days of post-cure, single layer tests for performance check were performed by evaluating hardness (Koenig pendulum), crosslink density (MEK double rub test) and bending performance (cone bending test). The tack-free, colorless coating films had dry thicknesses ranging from 25 to 60 μm with K-pendulum values of greater than 42 and MEK double rub values of greater than 380. Cone bend tests at all test diameters (diameters from 3.2 to 38.1 mm) showed no cracks in the individual coating layers.
[0072] Example 25: Coating composition and coating layer obtained after curing For a typical 2K system, composition A (57.8 g trimethylolpropane triacrylate, 36.1 g 1,6-hexamethylene diacrylate, 53.7 g blocked polyisocyanate crosslinker from Example 1, 7.2 g butyl acetate, and 45.2 g unsaturated polyester from Example 14) is added to composition B (0.4 g catalyst 9001, 60 mg catalyst Borchers Deca Manganese 8, 0.4 g BYK378) and mixed and stirred until a homogeneous mixture is obtained. The VOC value of the coating composition was measured to be 89 g / L. The mixture was spray applied to a tin test panel and baked at 140° C. for 20 minutes to obtain a tack-free film. After 3 days of post-cure, single layer tests for performance check were performed by evaluating hardness (Koenig pendulum), crosslink density (MEK double rub test) and bending performance (cone bending test). The tack-free, colorless coating films had dry thicknesses ranging from 25 to 60 μm with K-pendulum values of more than 84 and MEK double rub values of more than 500. Cone bend tests at all test diameters (diameters from 3.2 to 38.1 mm) showed no cracks in the individual coating layers.
[0073] <Performance test standards> 1.Hardness The pendulum damping test after Koenig or Persoz is used to mechanically measure the surface hardness of coatings. The hardness of a coating is determined by the number of oscillations made by a pendulum between two defined angles (6-3 degrees for the Koenig pendulum, 12-4 degrees for the Persoz pendulum). The number of oscillations increases with increasing hardness of the coating surface. The measurement method is standardized in ISO 1522.
[0074] 2. Solvent Love Test To evaluate crosslinking and ensure that the coating system has cured, a solvent rub test is performed using methyl ethyl ketone (MEK) as the solvent. This test is widely used in the coatings industry because it allows a quick relative assessment of the degree of cure without waiting for long-term exposure results. Rubs are counted as double rubs (one forward rub and one backward rub constitute a double rub) to give a measurable value of MEK resistance and degree of cure. A traditional 2K polyurethane or acid / epoxy clearcoat has an MEK double rub value of approximately 200 rubs.
[0075] 3. Bending test The bend test is used to determine the effect of bending on the elasticity, adhesion and extensibility of cured coatings on metal panels. The cone bend tester consists of a frame with a rollered bending lever that pivots on a steel conical mandrel with a diameter of 3.2 to 38.1 mm. The test specimen can be bent over part of the length of the mandrel or along the entire length of the mandrel and results (cracks) corresponding to the different test diameters can be observed in one operation.
[0076] 4.VOC testing A gravimetric method was applied to measure the volatile organic compounds (VOC) emission of the coating compositions. The VOC content was measured based on the mass loss of the composition when heated at 130° C. for 60 minutes.
[0077] 5. Rheological Testing The thixotropic effect of the sag control agent and coating composition was characterized using an Anton Paar rheometer. The 2D rheological profile was measured by fast shear rate change. The test was carried out at two different shear rates (shear rate 1 =1s -1 , shear rate 2 =1000s -1 The thixotropy index is a function of the high shear (η 2 ) and low shear (η 1 ) the ratio of the viscosity of the sample between
Claims
1. a). at least one polyisocyanate selected from aliphatic polyisocyanates, cycloaliphatic polyisocyanates, and polyisocyanate-functional polymers; b). At least one β-diketone which is ethyl 2-oxocyclopentanecarboxylate and / or α-acetylbutyrolactone; and and at least one (meth)acrylate having an amino group. A blocked polyisocyanate crosslinking agent obtained from the reaction of components comprising: A blocked polyisocyanate crosslinking agent obtained by reacting the resultant product obtained by reacting the above a) at least one polyisocyanate selected from aliphatic polyisocyanates, alicyclic polyisocyanates, and polyisocyanate-functional polymers with the above b) at least one β-diketone which is ethyl 2-oxocyclopentanecarboxylate and / or α-acetylbutyrolactone, with the above at least one (meth)acrylate having an amino group.
2. 2. The blocked polyisocyanate crosslinker of claim 1, wherein the polyisocyanate is at least one selected from hexamethylene diisocyanate, hexamethylene diisocyanate trimer, 4,4'-dicyclohexylmethane diisocyanate, and polyisocyanate-functional aliphatic acrylic esters.
3. The blocked polyisocyanate crosslinking agent according to claim 1, wherein the (meth)acrylate is at least one selected from 2-aminoethyl acrylate, 2-aminoethyl methacrylate, 2-(tert-butylamino)ethyl acrylate, 2-(tert-butylamino)ethyl methacrylate, N,N-diethylaminoethyl acrylate, N,N-diethylaminoethyl methacrylate, N,N-dimethylaminoethyl acrylate, N,N-dimethylaminoethyl methacrylate, 2,2,6,6-tetramethyl-4-piperidyl acrylate, and 2,2,6,6-tetramethyl-4-piperidyl methacrylate.
4. 4. The blocked polyisocyanate crosslinker of claim 3, wherein the (meth)acrylate is 2-(tert-butylamino)ethyl methacrylate.
5. The blocked polyisocyanate crosslinking agent according to any one of claims 1 to 4, wherein the molar ratio of the β-diketone to the (meth)acrylate is from 1:10 to 10:
1.
6. The following steps: i). Reaction of polyisocyanates with β-diketones; and ii). Reaction of the resulting product obtained in step i) with a (meth)acrylate; A method for preparing the blocked polyisocyanate crosslinker of any one of claims 1 to 5, comprising:
7. A). At least one blocked polyisocyanate crosslinker according to any one of claims 1 to 6; and B). at least one reactive diluent; 1. A coating composition comprising:
8. A). At least one blocked polyisocyanate crosslinker according to any one of claims 1 to 6; and C). at least one polyol; 1. A coating composition comprising:
9. A). at least one blocked polyisocyanate crosslinker according to any one of claims 1 to 6; B). at least one reactive diluent; and C). at least one polyol; 1. A coating composition comprising:
10. A). at least one blocked polyisocyanate crosslinker according to any one of claims 1 to 6; B). at least one reactive diluent; and D). At least one unsaturated polyester; 1. A coating composition comprising:
11. 11. The coating composition according to claim 10, further comprising at least one sag control agent having a solids content of 90% or more by weight, based on the total weight of the sag control agent.
Citation Information
Patent Citations
Photosetting coating composition
JP1983063760A
Cationic electrodeposition coating composition for casted product
JP1992018459A
Blocked polyisocyanate
JP2004035552A
New dual curing system
JP2006510786A
Reactive systems, their preparation and use
US20070083028A1